Pengaruh Metode Probing-Prompting terhadap Hasil Belajar PKN Murid Kelas IV SDN 30 Sumpang Bita - Rahmah Rahmah; Suardi Suardi; Rismawati Rismawati (Departement of Mathematics Education, 2023)
Problems with this study were the students' lack of enthusiasm for the learning process and poor learning outcomes in citizenship. The main objective of this study was to determine the impact of probing methods on learning outcomes in Class IV SDN 30 Sumpang Bita. This research method uses a mixed method of collecting data using quantitative and qualitative data results. The study informant used his 15 subject sample and the study participant used her 14 simple random sample. Google Forms surveys are used as a quantitative research tool. Qualitative measures are observations, interviews and documentation. The qualitative data analysis used consisted of data reduction, data display and quantitative data analysis, i.e. validity test. The results showed that the probing prompt was effective, as it was already in the high category with an offer rate of 79%. Therefore, this model makes students more active during the learning process. Think lively, discuss lively, and create better communication between teachers and students. The conclusion of this study is that the probing-prompt method has a significant impact on improving student learning outcomes.